2000
DOI: 10.5858/2000-124-0832-png
|View full text |Cite
|
Sign up to set email alerts
|

Primary Nodal Gastrinomas

Abstract: Background.—The term primary lymph node gastrinoma was first used to describe a group of patients with gastrin-producing tumors present in lymph nodes located in a well-defined anatomic region. The patients had no known primary tumors in the pancreas or gastrointestinal tract and had disease-free survival for up to 18 years. The anatomic region in question has a triangular shape that extends from the cystic and common bile ducts to the second and third portion of the duodenum and the neck and body of the pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Gastrinoma with Zollinger-Ellison syndrome is very rare in childhood and may originate from different locations: pancreatic parenchyma, lymphatic tissue, and submucosal duodenum within gastrinoma triangle. [1][2][3][4] Gastrinoma in lymph node makes it challenging to discriminate between primary and metastatic disease. 68 Ga-DOTA-peptide PET/CT is the investigation of choice for localization of primary and metastatic disease in gastrinoma and other NETs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrinoma with Zollinger-Ellison syndrome is very rare in childhood and may originate from different locations: pancreatic parenchyma, lymphatic tissue, and submucosal duodenum within gastrinoma triangle. [1][2][3][4] Gastrinoma in lymph node makes it challenging to discriminate between primary and metastatic disease. 68 Ga-DOTA-peptide PET/CT is the investigation of choice for localization of primary and metastatic disease in gastrinoma and other NETs.…”
mentioning
confidence: 99%
“…Existence of primary lymph nodal gastrinomas in several case reports/series without recurrence after complete surgical resection in long-term surveillance supported the hypothesis that sporadic gastrinoma arise from stem cells from the ventral pancreatic bud that gets dispersed into lymph tissue through migration within triangle area and stains for chromogranin, synpatophysin, and specific neuropeptide (eg, gastrin). Gastrinoma with Zollinger-Ellison syndrome is very rare in childhood and may originate from different locations: pancreatic parenchyma, lymphatic tissue, and submucosal duodenum within gastrinoma triangle [1][2][3][4]. Gastrinoma in lymph node makes it challenging to discriminate between primary and metastatic disease.68 Ga-DOTA-peptide PET/CT is the investigation of choice for localization of primary and metastatic disease in gastrinoma and other NETs 5,6.…”
mentioning
confidence: 99%
“…Pathologic data suggest that pancreatic lymph nodes contain neuroendocrine cells that have the same potential as pancreatic neuroendocrine cells and, in theory, can give rise to primary nodal gastrinomas. 5 Etiology of these primary lymph node gastrinomas remains controversial particularly because it may alter the patient's therapy. If the tumor arises primarily in a lymph node then enucleation may be curative, and this has been described.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrinoma triangle, a term coined in 1984 by Dr. Stabile, is bounded by the common bile duct, the second and third portions of the duodenum, and the pancreas 2 . Analysis by both Herrmann et al 4 and Perrier et al 1 have immunohistochemically examined patients without known gastrinomas and found that lymph nodes from this triangle stain for gastrin, chromogranin A, pancreatic protein, and synaptophysin, specific makers for neuroendocrine cells. It is believed that nests of cells become entrapped within these lymph nodes when the ventral pancreatic bud rotates during fetal life 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although controversial, some authors believe that primary lymph node gastrinomas exist. [1][2][3][4] In support of this theory, 40% to 50% of patients without known primary lesions can be biochemically cured with peripancreatic lymphadenectomy. 2 We present a case of a patient with refractory peptic ulcer disease and elevated serum gastrin levels who on an octreotide scan demonstrated uptake near the pancreas as well as a focus within the left supraclavicular neck.…”
mentioning
confidence: 99%